EVALUATION TOWARDS LEARNING PROCESS FOR DIGITAL LEARNING DEVELOPMENT IN CURRICULUM AND INSTRUCTION COURSES - Dewi, Laksmi (EDUTECH, 2021)
An effective learning process is conducted through planning, management, implementation, monitoring, and evaluation to result in feedback. Reflection as a form of evaluation is carried out to provide input in improving the further learning process. This study aims to evaluate learning, especially on the components of the objectives, material, process, learning evaluation, faced obstacles during the learning process, and expectations for the next lecture, one of Educational Basic Learning Course (EBLC) called Curriculum and Instruction course. This process is done as the basis for the development of digital learning in online learning in the future. Data were obtained by distributing questionnaires to 24 lecturers teaching in the curriculum and learning courses. It is a group of compulsory courses that all students are necessary to be included in their study at one of the state universities whose core business is in education. Based on the research data, it is found that 1) the learning achievement has been compiled according to the educational competencies listed in the Semester Lecture Design (RPS) used by all lecturers in carrying out the learning process. 2)Â  the learning material has been systematically set as stated in the RPS to facilitate the organization of material in learning, 3) the learning implementation by lecturers uses various learning methods focusing on student-centered learning, 4). The evaluation performance is done using Computer Based Test (CBT) with developed questions regarding specified learning outcomes, 5) the obstacles faced by administrators of Curriculum and Instruction course are the number of continuously growing classes and lacking the number of lecturers for each semester. Moreover, it is also essential to improve students' learning motivation to achieve maximum learning outcomes. It is expected that learning innovations can assist them in improving the quality of learning by developing digital learning media and supporting blended learning between face-to-face and online learning using the Learning Management System (LMS)